Community Building Through Inclusive Music-Making - Gosine, Jane; Hawksley, Deborah; LeMessurier Quinn, Susan (Voices: A World Forum for Music Therapy, 2017)
The objective of this project was to expand the boundaries of regular music therapy sessions at a non-profit organization to include performances and workshops with community musicians. The goals and practices used for persons with physical disabilities prepared participants to benefit from inclusive music-making with local community musicians who had no previous music therapy experience, but whose performing styles were closely aligned with the musical preferences of our participants. The four collaborative workshops, which were held over six months, involved music therapy participants, accredited music therapists, local musicians, and volunteers engaging in music making together where teaching and learning was shared amongst all involved. The workshops were also an important mechanism for raising greater awareness of the needs and abilities of the music therapy participants.